EMPAT RISALAH SYEKH MUKHTAR AMBAI: Pribumisasi Fikih Melalui Aksara Arab-Melayu di Kerinci - nuzul iskandar (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2022)
This study was triggered by the thought that the works of Syekh Mukhtar Ambai Kerinci were important to mention, in addition to the general reason that so far the ancient texts from Kerinci tended to only deal with traditional issues and very little about religious issues, as well as the specific reason that Mukhtar's works shows the tendency of fiqh indigenization towards the Kerinci community. This study aims to see how the method of writing fiqh materials in Sheikh Mukhtar Ambai's four treatises, and their correlation with the method of fiqh indigenization to the Kerinci community. This study shows that the works of Syekh Mukhtar Ambai very strongly represent the efforts to indigenize fiqh in the community. The indications of fiqh indigenization can be captured in three ways. First, writing that does not follow fiqh systematics, but is adapted to the needs of the community. Second, linking the discussion of fiqh with monotheism and Sufism according to the psychological needs of the community which requires strengthening the understanding of amaliyah in terms of monotheism and Sufism. Third, using local terms so that his work is easy to understand and familiar with people's daily lives.Keywords: Arabic-Malay Treatise; Indigenization of Fiqh; Kerinci; Mukhtar Ambai.